Pedagogical Views and Educational Activities of Ismail Gasprinsky - Мухиддин Хайруддинов (Lietuvos Istorijos Studijos)
The article deals with the pedagogical and educational activities of the outstanding son of the Crimean Tatar people Ismail Gasprinsky (1851–1914). Accumulating the achievements of the advanced pedagogical practice of Europe, I. Gasprinsky acted as a spokesman for the need for socio-economic changes in the countries of the East. I. Gasprinsky spoke up for the synthesis of Muslim doctrine and the achievements of modern science, he created and led the Jadid pedagogical movement aimed at the transition from confessional and Russian civic education to the creation of a national secular education.